Carcass traits and some blood stress parameters of summer stressed growing male rabbits of different breeds in response to boldenone undecylenate - Abdel-Hamid, Tamer Mohamed; Farahat, Mahmoud Hosney (Journal of Advanced Veterinary and Animal Research, 2015)
The present study was conducted to investigate the effects of boldenone undecylenate (BUL) on carcass traits and blood stress parameters in growing male rabbits. A total of 170 male rabbits comprising of three breeds namely New Zealand White (NZW; n=55), Californian (CAL; n=50), and Rex (RX; n=65) were taken for this study. The rabbits of each breed were divided into three groups viz., D0 (control), D1 provided with normal dose of BUL (at 4.4 mg/kg body weight), and D2 provided with BUL (at 8.8 mg/kg bwt). The rabbits were kept under temperature ranged from 28-32°C during the experimental period. Carcass traits of the rabbits were studied, and the blood parameters were measured by radioimmunoassay. Most of carcass traits, globulin and cholesterol levels in the serum were significantly improved for the injection of BUL at normal dose. Plasma corticosterone levels in normal dose injected rabbits were lowered by 27.21 and 15.25% as compared to controls and double dose, respectively. The effect of interaction between dose and breed was non-significant (P>0.05) on almost all carcass traits and blood parameters. In conclusion, BUL improves all carcass traits in male growing rabbits when injected with normal dose of BUL, with the exception of dressing-out%, and has a significant lowering effect on stress hormone (i.e., corticosterone), and increasing effect on serum total protein, globulin and cholesterol. DOI: http://dx.doi.org/10.5455/javar.2015.b64